The Metamorphosis of Confucian Philosophy - Andrijauskas, Antanas (Acta Orientalia Vilnensia, 2003)
The article is intended to display genesis and uniqueness of the philosophical tradition of Confucianism. Unlike the intellectual tradition of Taoism, which experienced a religious influence, that of Confucian tradition (Mengzi, Xunzi, Zhu Xi, Zhou Dunyi and others) almost always preserved its autonomy in regard to religion. Distinctive features of Confucian philosophical tradition, that are immediately noticeable in comparison to other intellectual traditions, are the prominence of social, political, and ethical problems, emphatic naturalism. The exceptional attention is given to the relationship between man and the natural world around him. Various maitres of Confucian philosophy regard the world of nature as a seamless, harmonious system that functions according to its own Taoist laws, which have been formed through the ages. Thinkers of Confucian intellectual tradition perceive the phenomena of the world in their totality, in a stream of the five primordial elements and of the metamorphoses of other phenomena of being, in the coherence of their component parts. Everything in the world is interconnected and is in a process of constant change. These different ways of understanding reality are reflected in the fundamental philosophical categories that give meaning to the processes of the world.